Adaptation and Psychometric Analysis of the Workaholism Scale for Workers in Indonesia - Asmi, Tri Wira Gustari; Kadiyono, Anissa Lestari (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This study aimed to adapt the workaholism measure instrument and examine the psychometric results to be tested on employees and workers in Indonesia. This measure has been tested and applies to workers in various occupational fields in the United States. The workaholism measurement instrument was developed by Clark, Smith, and Haynes (2020) and has never been adapted for the population in Indonesia. The process of adapting this measuring instrument refers to the International Test Commission. The participants in this study were 102 workers in Indonesia using the incidental sampling technique. The adapted scale is reliable, with a Cronbach's alpha of .931. In the Confirmatory Factor Analysis (CFA) results, the fit model is acceptable (RMSEA = .70, CFI = .96), which indicates that the data are consistent with the research hypothesis. The results of adapting the workaholism scale into Indonesian have a different number of items from the original measuring instrument, namely 13. Evidence through confirmatory factor analysis shows that the workaholism measurement model can be represented in the Indonesian population from four dimensions: motivational, cognitive, emotional, and behavioral.